Molecular characterisation of Rhipicephalus sanguineus (ACARI: IXODIDAE), and occurrence of pathogens in ticks and host dogs / Prakash Batah Kunalan - Prakash , Batah Kunalan (2019)
The brown dog tick, Rhipicephalus sanguineus is one of the ubiquitous ticks in the world and it is a well-recognized vector of many tick-borne diseases affecting dogs and occasionally humans. The taxonomic status of R. sanguineus has been long debated, there is a consensus that the populations of this tick species should be referred to as R. sanguineus sensu lato (s.l.) until its taxonomic status is resolved. The existence of two divergent lineage, the southern lineage and northern lineage in R. sanguineus isolates indicates the genetic variability of R. sanguineus s.l. The aims of the study were to molecularly characterize R. sanguineus in Malaysia by determining its lineage and detect various pathogens in R. sanguineus and host dogs. Phylogenetic analysis indicated that all R. sanguineus from Peninsular Malaysia fall into the northern lineage. Low genetic diversity was observed in this isolate as inferred from the cytochrome oxidase subunit I (COI) and 16S ribosomal RNA (16S) genes. For pathogen detection, tick and dog blood samples were molecularly screened for the presence of pathogenic bacteria Rickettsia, Ehrlichia, Anaplasma, and protozoa Babesia and Hepatozoon. In the present study, Rickettsia asembonensis, Ehrlichia canis, Anaplasma platys, Babesia gibsoni, Babesia vogeli, and Hepatozoon canis were detected at varying frequencies. The prevalence of R. asembonensis, E. canis, A. platys, B. gibsoni, B. vogeli and H. canis in R. Sanguineus ticks were as follows, 1.43%, 0.71%, 2.86%, 1.43%, 1.43% and 0.71%, respectively. For the dog blood samples, the prevalence was 12. 92% for E. canis, 3.33% for A. platys, 2.08% for B. canis, and 3.33% for H. canis. None of the blood samples were tested positive for Rickettsia asembonensis. Results from the present study indicated that a variety of tick-borne diseases are present in Malaysian dogs and R. sanguineus may act as the potential vector in transmitting these diseases.